Tourism studies on Łódź and its metropolitan area - Liszewski, Stanisław (Turyzm/Tourism, 2015)
This paper is an overview, and its aim is to identify published research works on tourism in Łódź and around the city as well as the tourism trips of the city’s inhabitants. This target allowed around 100 articles to be gathered which have been divided into eight thematic groups and analysed for merit. Their names are the titles of subchapters: the city’s tourism resources, land use planning, tourism space, the tourism activity of the citizens of Łódź, the tourism product – tourism development strategies, and tourism research of surrounding areas in the metropolitan area of Łódź. In the final part, the author divides the research into stages leading up to an explanation of the current development of research on Łódź and its metropolitan area and then suggests further research directions.